2019
DOI: 10.3390/cells8090998
|View full text |Cite
|
Sign up to set email alerts
|

Capture and Detection of Circulating Glioma Cells Using the Recombinant VAR2CSA Malaria Protein

Abstract: Diffuse gliomas are the most common primary malignant brain tumor. Although extracranial metastases are rarely observed, recent studies have shown the presence of circulating tumor cells (CTCs) in the blood of glioma patients, confirming that a subset of tumor cells are capable of entering the circulation. The isolation and characterization of CTCs could provide a non-invasive method for repeated analysis of the mutational and phenotypic state of the tumor during the course of disease. However, the efficient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 70 publications
1
62
0
Order By: Relevance
“…VAR2CSA has a high affinity to chondroitin sulfate proteoglycans proposed to be uniquely expressed on cancer cells. The study isolated CTCs in comparable numbers to our study [17]. Of note, MCSP belongs to the chondroitin sulfate proteoglycan protein family and our data confirm high expression on some GBM cell lines but total lack on others, highlighting that targeting more than one cell surface protein should be considered advantageous for GBM-CTC isolation.…”
Section: Discussionsupporting
confidence: 79%
“…VAR2CSA has a high affinity to chondroitin sulfate proteoglycans proposed to be uniquely expressed on cancer cells. The study isolated CTCs in comparable numbers to our study [17]. Of note, MCSP belongs to the chondroitin sulfate proteoglycan protein family and our data confirm high expression on some GBM cell lines but total lack on others, highlighting that targeting more than one cell surface protein should be considered advantageous for GBM-CTC isolation.…”
Section: Discussionsupporting
confidence: 79%
“…This study therefore set out to explore and optimize different technical parameters and approaches for rVAR2-based cancer cell isolation. We have previously shown that rVAR2-coated paramagnetic beads can isolate CTCs from clinical cancer patient blood samples [12,26]. However, in this study, the aim was to further optimize the technical parameters to obtain the highest level of assay performance and the required reproducibility, as well as paving the way for a standardized optimization method of bead coupling to rVAR2, which could also inspire development strategies of other bead-coupled CTC-targeting moiety technologies.…”
Section: Discussionmentioning
confidence: 99%
“…VAR2CSA was produced in two recombinant versions (rVAR2), DBL1-ID2a and ID1-ID2a, in SHuffle®T7 Competent E. coli as previously described [12]. Both constructs include a C-terminal hexa His-tag and V5 tag, as well as an N-terminal SpyTag.…”
Section: Protein Production and Quality Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although extracranial metastases in glioma patients are rarely observed, recent studies have shown the presence of CTCs in the bloodstream. Bang-Christensen et al demonstrated how the recombinant malaria VAR2CSA protein (rVAR2) can be used for the capture and detection of glioma cell lines and identified a panel of proteoglycans, known to be essential for glioma progression [7]. Cerebrospinal fluid (CSF) is one of the promising diagnostic targets because CSF passes through the central nervous system, harvests tumor-related markers from brain tissue and then, delivers them into peripheral parts of the human body where CSF can be sampled using minimally invasive and routine clinical procedure.…”
mentioning
confidence: 99%